2017
DOI: 10.1007/s00109-017-1589-2
|View full text |Cite
|
Sign up to set email alerts
|

A 15-amino acid C-terminal peptide of beta-defensin-3 inhibits bone resorption by inhibiting the osteoclast differentiation and disrupting podosome belt formation

Abstract: HBD3-C15 inhibits osteoclast differentiation and bone resorption capacity. HBD3-C15 disrupts the podosome belt formation in osteoclasts. HBD3-C15 alleviates the bone loss by RANKL or A. actinomycetemcomitans LPS in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
0
11
0
2
Order By: Relevance
“…To overcome these limitations and identify the active peptide fragments within HBD3, the C-terminal HBD3 peptide was modified by substituting serine for cysteine residues, and shown to have retained its anti-microbial activity [42]. Recent reports showed that HBD3-C15 peptide could attenuate LPS-induced bone resorption, by disrupting podosome belt formation in osteoclasts and suppressing their differentiation [43]. In anti-inflammatory effect, HBD3-C15 did not affect upregulated TLR-2 level and its following signaling pathways in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations and identify the active peptide fragments within HBD3, the C-terminal HBD3 peptide was modified by substituting serine for cysteine residues, and shown to have retained its anti-microbial activity [42]. Recent reports showed that HBD3-C15 peptide could attenuate LPS-induced bone resorption, by disrupting podosome belt formation in osteoclasts and suppressing their differentiation [43]. In anti-inflammatory effect, HBD3-C15 did not affect upregulated TLR-2 level and its following signaling pathways in this study.…”
Section: Discussionmentioning
confidence: 99%
“…5-6), which subsequently leads to the attenuation of NFATc1 and c-Fos. NFATc1 and c-Fos are two crucial transcription factors that regulate osteoclast differentiation [31]. Furthermore, RANKL upregulated osteoclast-specific genes Cathepsin K and MMP9, which were reduced by ChondroT and its five constituent herbs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…shown the potential to be a therapeutic agent for the inhibition of bone destruction (Park et al, 2017). Several synthesized cathelicidins from cattle (BMAP28), sheep (SMAP28 and SMAP29) and pigs (PMAP23) have shown broad-spectrum antimicrobial activities (Brogden et al, 2007).…”
Section: Artificial Antimicrobial Peptidesmentioning
confidence: 99%